2023
DOI: 10.5114/bta.2023.127202
|View full text |Cite
|
Sign up to set email alerts
|

Potent antifungal properties of gallic acid in Sarcochlamys pulcherrima against Candida auris

Abstract: Candida auris is a major public health concern due to its high transmission and mortality rates, as well as the emergence of pan-resistant strains. This study aimed to identify an antifungal compound from Sarcochlamys pulcherrima , an ethnomedicinal plant, that can inhibit the growth of C. auris . Methanol and ethyl acetate extracts of the plant were obtained, and high-performance thin-layer chromatography (HPTLC) analysis was conducted to identify the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Few studies reported that, 3-pentanol and 6-pentyl-α-pyron volatiles produced by Bacillus amyloliquefaciens strain IN937a and Trichoderma, respectively, induce systemic resistance via modulation of salicylic acid and jasmonic acid pathways resulting in reduction of phytopathogenic attack in pepper and Arabidopsis thaliana [ 44 , 45 ]. Many phenols such as gallic acid were reported to protect plant from fungal pathogen by degrading fugal chitin by enhancing the activities of chitinases and peroxidases [ 46 , 47 ]. From aforementioned reports, it was clear that our finding of increased level of phenols in volatiles treated plants was indication of elevated defense response against fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported that, 3-pentanol and 6-pentyl-α-pyron volatiles produced by Bacillus amyloliquefaciens strain IN937a and Trichoderma, respectively, induce systemic resistance via modulation of salicylic acid and jasmonic acid pathways resulting in reduction of phytopathogenic attack in pepper and Arabidopsis thaliana [ 44 , 45 ]. Many phenols such as gallic acid were reported to protect plant from fungal pathogen by degrading fugal chitin by enhancing the activities of chitinases and peroxidases [ 46 , 47 ]. From aforementioned reports, it was clear that our finding of increased level of phenols in volatiles treated plants was indication of elevated defense response against fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%